Three new species of squat lobsters of the genus Fennerogalathea Baba, 1988 (Decapoda: Galatheidae) from the Pacific Ocean - Rodriguez-Flores, Paula C.; Machordom, Annie; Macpherson, Enrique (Zootaxa, 2017)
The genus Fennerogalathea Baba, 1988 was known to contain two species: F. chacei Baba, 1988, the type species, from the Philippines, Taiwan and Indonesia and F. chirostyloides Tirmizi & Javed, 1993 from the Bay of Bengal. In the present study, three new species of the genus are described and illustrated: F. chani n. sp. from Papua New Guinea, F. cultrata n. sp. from New Caledonia and Vanuatu and F. ensifera n. sp. from Fiji. The new species are morphologically distinguishable on the basis of the shape and spination of the rostrum and the presence/absence of a small spine on the frontal margin of the carapace. The species also show clear genetic differences (COI and 16S rDNA) among them.